Integration of Religious Character in Learning at Nature Schools - Lukman Hakim Lubis; Chairul Amriyah; Muhammad Muchsin Afriyadi; Ridho, Ilham Syaifur (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2026)
This article systematically reviews previous studies on the integration of religious character values in learning at Nature-Based Schools using the Systematic Literature Review (SLR) method. Data were collected from Google Scholar via Publish or Perish 8 (limited to journals indexed in Sinta 2 and above) and from Scopus through direct database searches. The literature selection followed the PRISMA 2020 protocol, yielding 4 eligible studies. Data were analyzed using NVivo 15 through four thematic analysis stages: coding, categorizing, interpreting, and thematic mapping. The findings reveal that the five dimensions of religiosity proposed by Glock and Stark—belief, knowledge, experience, practice, and consequences are comprehensively implemented in learning at Nature-Based Schools. Belief and knowledge serve as spiritual and intellectual foundations, while experience, practice, and consequences are reflected in students’ moral and reflective behaviors. The integration of these values is realized through Experiential Learning as the core foundation, where learning occurs through direct experience, reflection, and socio-spiritual engagement. This approach encompasses the Humanistic Approach, Contextual Teaching and Learning (CTL), Religious Spiritual Approach, and Ecopedagogical Approach, which internalize religious values through social projects, outdoor learning, salat dhuha, charity, and positive habituation. Teachers act as moral exemplars and value facilitators. Overall, Experiential Learning proves effective in fostering holistic religious character formation.